Shopping versus Nature? An Exploratory Study of Everyday Experiences - Craig, Tony P.; Fischer, Anke; Lorenzo-Arribas, Altea (Frontiers in Psychology, 2018)
Although a growing volume of empirical research shows that being in nature is important for human 11 wellbeing, the definition of what constitutes an 'experience in nature', and how this is different from 12 other types of experiences, is very often left implied. In this paper we contrast everyday experiences 13 involving nature with a category of everyday experience in which most people regularly partake. We 14 present an exploratory study in which people (N=357) were explicitly asked to describe a memory 15 they had of an everyday ‘experience which involved nature’, as well as an everyday 'experience 16 which involved shopping’. The open-ended responses to these questions were analysed both 17 quantitatively and qualitatively. Nature experiences were generally found to be more positive than 18 shopping experiences, and they were more likely to be rated as ‘peaceful’ and ‘active’ compared to 19 shopping experiences. Follow-up analyses indicate a significant interaction between experience 20 category (nature or shopping), and the relationship between connectedness to nature and the amount 21 of pleasure associated with that experience: The more strongly connected to nature a respondent was, 22 the larger the disparity between the pleasantness of the shopping experience and that of the 23 experience in nature tended to be.